2010
DOI: 10.1021/nl1010977
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Photodetector Based on GaN/AlN Quantum Disks in a Single Nanowire

Abstract: We report the demonstration of single-nanowire photodetectors relying on carrier generation in GaN/AlN QDiscs. Two nanowire samples containing QDiscs of different thicknesses are analyzed and compared to a reference binary n-i-n GaN nanowire sample. The responsivity of a single wire QDisc detector is as high as 2 x 10(3) A/W at lambda = 300 nm at room temperature. We show that the insertion of an axial heterostructure drastically reduces the dark current with respect to the binary nanowires and enhances the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
116
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(130 citation statements)
references
References 15 publications
13
116
1
Order By: Relevance
“…2 Ultra-violet photodetectors based on a single GaN NW containing quantum discs have also been reported. 3 New possibilities for wavelength tuning have been offered with the demonstration of GaN NW-ring lasers. 4 The unique geometry and properties of semiconductor NWs have motivated their use for new applications, such as nanoscale photodetectors with high polarization degree of detection.…”
Section: Introductionmentioning
confidence: 99%
“…2 Ultra-violet photodetectors based on a single GaN NW containing quantum discs have also been reported. 3 New possibilities for wavelength tuning have been offered with the demonstration of GaN NW-ring lasers. 4 The unique geometry and properties of semiconductor NWs have motivated their use for new applications, such as nanoscale photodetectors with high polarization degree of detection.…”
Section: Introductionmentioning
confidence: 99%
“…14 In comparison with planar devices, almost defect-free semiconductor nanowires open the possibility of exploiting the photoconductive gain while avoiding the deleterious effects of grain boundaries and dislocations on the spectral response. 18 Both ZnO and (Al,Ga)N are promising choices to be used as miniature, visible-blind, ultraviolet (UV) photosensors, [11][12][13][14]16,19 but GaN presents advantages in terms of physical and chemical robustness as well as for controlled doping.…”
mentioning
confidence: 99%
“…[15][16][17][18] Nanowires, furthermore, represent a model system for atom probe analysis, 19-24 as they closely approximate the shape of a field-emission tip. Nevertheless, and despite the interest of nanowire-based QDs for quantum information [25][26][27][28][29] and for their integration in nanoscale optoelectronic devices, [30][31][32][33] no studies of nanowire QDs by APT have been reported yet.Core-shell GaAs/AlGaAs nanowires grown by molecular beam epitaxy (MBE) have been shown to exhibit narrow luminescence and single photon emission, ascribed to QDs forming occasionally at the external corners of the AlGaAs shells. 27 Isolated emissions centered around 670 nm ($1.85 eV) could be found by cathodoluminescence (CL) spectroscopy, with a typical mean frequency along the axis of the order of one spot per micron.…”
mentioning
confidence: 99%